2016
DOI: 10.1371/journal.pbio.2000504
|View full text |Cite
|
Sign up to set email alerts
|

Cyp26 Enzymes Facilitate Second Heart Field Progenitor Addition and Maintenance of Ventricular Integrity

Abstract: Although retinoic acid (RA) teratogenicity has been investigated for decades, the mechanisms underlying RA-induced outflow tract (OFT) malformations are not understood. Here, we show zebrafish embryos deficient for Cyp26a1 and Cyp26c1 enzymes, which promote RA degradation, have OFT defects resulting from two mechanisms: first, a failure of second heart field (SHF) progenitors to join the OFT, instead contributing to the pharyngeal arch arteries (PAAs), and second, a loss of first heart field (FHF) ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 82 publications
6
58
0
Order By: Relevance
“…7D), as previously reported (Stennard et al, 2005), whereas Col5a2 was specifically at the venous pole (Fig. 7B), and Mmp9, which is required for the addition of precursor cells in the fish heart tube (Rydeen and Waxman, 2016), was detected in the mouse heart field (Fig. 7C).…”
Section: Nodal Modulates Cell Proliferation Differentiation and Extrsupporting
confidence: 86%
“…7D), as previously reported (Stennard et al, 2005), whereas Col5a2 was specifically at the venous pole (Fig. 7B), and Mmp9, which is required for the addition of precursor cells in the fish heart tube (Rydeen and Waxman, 2016), was detected in the mouse heart field (Fig. 7C).…”
Section: Nodal Modulates Cell Proliferation Differentiation and Extrsupporting
confidence: 86%
“…However, further studies in the zebrafish have revealed important roles in cardiac lineage commitments within the early anterior lateral plate mesoderm (APLM) and requirements for ventricular cardiomyocyte contributions from both first and second heart field sources [251,347].…”
Section: Pharyngeal and Cardiovascular Systemsmentioning
confidence: 99%
“…Furthermore, reduced proliferation and expression of FGF8 was observed in cyp26a1/c1 knockdown embryos. This SHF-driven part of the ventricular loss could be partially rescued by restoring expression of FGF8 which is required for SHF progenitor proliferation [347].…”
Section: Pharyngeal and Cardiovascular Systemsmentioning
confidence: 99%
“…SHF, second heart field F I G U R E 2 Segments of the second heart field (SHF) and signaling regulating anterior SHF development. Either an excess or lack of RA causes conotruncal heart defects as well as aortic arch anomalies (derivatives of posterior pharyngeal arch arteries), indicating that properly controlled RA signaling is required for normal OFT development (Irie et al, 1990;Lammer et al, 1985;Rydeen & Waxman, 2016;Sakabe et al, 2012;Taylor et al, 1980;Wilson & Warkany, 1949;Yasui et al, 1995). The posterior SHF provides heart progenitors giving rise to the atria and dorsal mesenchymal protrusion (DMP).…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggested that the fate of heart progenitors in each pharyngeal region appears to be defined before migration. Therefore, impaired development of a certain region of the anterior SHF causes a specific spectrum of con- Either an excess or lack of RA causes conotruncal heart defects as well as aortic arch anomalies (derivatives of posterior pharyngeal arch arteries), indicating that properly controlled RA signaling is required for normal OFT development (Irie et al, 1990;Lammer et al, 1985;Rydeen & Waxman, 2016;Sakabe et al, 2012;Taylor et al, 1980;Wilson & Warkany, 1949;Yasui et al, 1995). Mouse lines with an RARE-lacZ transgene showed that RA signaling is activated in the caudal anterior SHF at the posterior pharyngeal arches level (Guris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%